Healthy Eating: Scrambling for Healthy Beverages - Emily Minton (EDIS)
Unscramble the beverages below and determine which drinks you can have anytime and which ones you should limit! This 1-page fact sheet was written by Emily Minton and published by the UF Department of Family, Youth and Community Sciences, April 2012.